2018
DOI: 10.1055/s-0038-1636515
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Peripheral Vascular Disease

Abstract: In the past 20 years, peripheral artery disease (PAD) has been increasingly recognized as a significant cause of morbidity and mortality in the United States. PAD has traditionally been identified as a male-dominant disease; however, recent population trends and studies in PAD suggest that women are affected at least as often as men. Women comprise a larger population of the elderly than men, as well as an increasing proportion of patients with PAD. Much of the existing research on PAD has focused on whole pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 70 publications
4
39
0
3
Order By: Relevance
“…In iliac occlusive disease, studies have shown better outcomes with PTA and stenting compared with PTA alone. Interestingly, although women tend to present at an older age with iliac disease and have more extensive occlusive disease, PVI outcomes and stent patency did not differ in women compared to men [17,20,22]. SFA lesions longer than 10 cm are best treated with PTA and stenting as studies have demonstrated better patency rates compared to PTA alone.…”
Section: Percutaneous Transluminal Angioplastymentioning
confidence: 98%
See 3 more Smart Citations
“…In iliac occlusive disease, studies have shown better outcomes with PTA and stenting compared with PTA alone. Interestingly, although women tend to present at an older age with iliac disease and have more extensive occlusive disease, PVI outcomes and stent patency did not differ in women compared to men [17,20,22]. SFA lesions longer than 10 cm are best treated with PTA and stenting as studies have demonstrated better patency rates compared to PTA alone.…”
Section: Percutaneous Transluminal Angioplastymentioning
confidence: 98%
“…Indications for revascularization therapy include critical limb ischemia (CLI), rest pain, gangrene, or refractory claudication [17]. Historically, surgery had been the revascularization choice in these patients.…”
Section: Endovascular Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Sex specific risk factors include use of oral contraceptives, history of complications during pregnancy such as intrauterine growth restriction, preeclampsia, and pregnancy-induced hypertension. In lower extremities revascularization women may be more prone to complications because of either open or endovascular revascularization; although Endovascular intervention generally in females appears to be associated with better patency rates [ 62 ].…”
Section: Women and Peripheral Artery Disease (Pad)mentioning
confidence: 99%